Institute of Mathematics of The Ukrainian National Academy of Sciences: 60 years of development - Mitropolskiy, Yu. A.; Samoilenko, A. M.; Strok, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
In this brief historical essay, we describe main stages of the formation and development of the Institute of Mathematics of the Ukrainian National Academy of Sciences from its foundation in 1934 till now. Our attention is mainly focused on the achievements of its leading scientists and main directions of mathematical researches carried out in the Institute of Mathematics.